The relationship among the nominal rates of interest, the real rates of interest and the inflation rates: an empirical study of the fisher effect on the Malaysian T Bill Market - Noor Azlan Ghazali (Penerbit Universiti Kebangsaan Malaysia, 1990)
The Fishenan hypothesIs assert's that, If the expected real rate if interest is constant and therefore independent of expected inflation, each percentage pOint rise in the expected inflation 'esults in a percentage point rise in the nominal rate of interest. This paper tests the validity of the hypothesis on the Malaysian T Bill market. In conjunction to that, the interactions of the three variables, namely, nominal rate of interest, real rate of interest and the price -level were explored. This study found that the positive response of nominal rate toward the expected inflation increases gradually as maturity increases. In contradiction to the Fisher effect, the expected rate of lnflation was found to be a major determinant factor or the expected real rate, instead of the nominal rate. Thus, a nonvariant character of the real rate is rejected. In addition, past inflation rates do not possess any valuable information in forecastingfuture nominal or real rates. The sign of inefficiency in the market exists since the nominal rate is unable to summarize all information from previous price levels.